Analysis of the Impact of Contextual Teaching and Learning Integrated with Quizizz on High School Students’ Learning Outcomes - Humairah, Nur Aisyah; Rosman, Andi; Amir, Faizal; Kalsum, Ummu; Ilda, Ilda (Universitas Muhammadiyah Makassar, 2025)
Physics education often faces persistent challenges in enhancing students' engagement and conceptual understanding, especially when abstract topics are taught through traditional, teacher-centered approaches. This study addresses these issues by investigating the impact of integrating the Contextual Teaching and Learning (CTL) model with the gamified digital platform Quizizz on student learning outcomes in high school physics. Employing a true experimental pretest-posttest control group design, the study involved 54 Grade XII students at SMA Negeri 1 Malunda, divided into an experimental group (CTL with Quizizz) and a control group (direct instruction). Data were collected using a validated multiple-choice test (validity = 90.81%, reliability = 0.82) and analyzed through descriptive and inferential statistics, including N-Gain and t-tests. The results showed a significant improvement in the experimental group's average posttest scores (from 41.39 to 59.57), with an N-Gain of 0.30 (moderate), compared to the control group's minimal increase (from 49.96 to 49.31), with an N-Gain of 0.07 (low). Statistical tests confirmed a significant difference between the groups (p < 0.05). This study demonstrates that combining CTL and Quizizz not only supports conceptual learning through real-world contexts but also increases motivation and active participation through interactive gamification. The novelty of this research lies in the effective integration of CTL with digital gamified tools to enhance physics instruction. The findings contribute to the advancement of physics education by providing empirical evidence for adopting CTL-Quizizz as a powerful instructional strategy to enhance conceptual understanding and academic achievement in secondary education.